L’occasione e l’eterno: la tenda di Tolomeo Filadelfo nei palazzi di Alessandria. Parte seconda. Una proposta di ricostruzione (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The work is the second part of an essay published in “Lanx” 1 (2008).After exposing the previous reconstructions, a new proposal is advanced, which explains the marquee through the macedonian architecture and suggests a new architectonical building type, the oecus aegyptius. Since only the interior is known, the dimensions are calculated (m 34 x 26 approximately for the base, m 22 for the height of the columns, with the addition of the roof), and the constitutive elements are interpreted according to the comparison with the archaeological and literary evidence: the palm- and thyrsos-shaped columns, the nymphai and the antra, the statue bases, the arch door, the lacunar ceiling, the sloping roof, the furniture, the gold and silver vases, the works of art. The exhibition lasts one year, and consequently becomes a new “event”, in connection with the contemporary dionysiac pompé: the works of art acquire a new meaning, connoting the Lagides as refined collectors, and are part of a cultural and political program, probably organized by the Museum scholars. The exhibition, indeed, is marked by an encyclopaedical purpose: on one hand it seems to be the ephemeral equivalent of the  Museum and of the zoo promoted  by Ptolemy I, on the other it takes part in the cultural construction of the Ptolemean family, being almost its dynastic monument.
Keywords: Macedonian palaces; oecus aegyptius; hestiatoria; Sikyonian paintings; textiles; Alexandria Museum; ancient museology; alexandrian art